2016
DOI: 10.1021/acs.langmuir.5b04151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental–Theoretical Approach to the Adsorption Mechanisms for Anionic, Cationic, and Zwitterionic Surfactants at the Calcite–Water Interface

Abstract: The adsorption of surfactants (DTAB, SDS, and CAPB) at the calcite-water interface was studied through surface zeta potential measurements and multiscale molecular dynamics. The ground-state polarization of surfactants proved to be a key factor for the observed behavior; correlation was found between adsorption and the hard or soft charge distribution of the amphiphile. SDS exhibits a steep aggregation profile, reaching saturation and showing classic ionic-surfactant behavior. In contrast, DTAB and CAPB featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…31 In polymer coating, the electrostatic interaction sometimes plays crucial role to afford a durable modified surface by formation of polyion-complexes. [32][33][34] Furthermore, it is reported that annealing treatment of coating surface with polymers enhances electrostatic interaction by structural arrangement of polymers due to their flexibility. 35 The surface of PDMS treated by air-plasma is known to be silica-like, but the molecule at the surface seems to be flexible enough to recover hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…31 In polymer coating, the electrostatic interaction sometimes plays crucial role to afford a durable modified surface by formation of polyion-complexes. [32][33][34] Furthermore, it is reported that annealing treatment of coating surface with polymers enhances electrostatic interaction by structural arrangement of polymers due to their flexibility. 35 The surface of PDMS treated by air-plasma is known to be silica-like, but the molecule at the surface seems to be flexible enough to recover hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The positive and negative charge is strongly localized on nitrogen and oxygen atoms, respectively. As discussed by Durán-Álvarez et al [ 20 ], such a strong charge localization reflects a hard electrostatic nature of atoms being the charge carriers in C n (DAPANO) 2 and C n PDA. There is, however, an important difference in charge distribution between C n (DAPANO) 2 and C n PDA.…”
Section: Resultsmentioning
confidence: 97%
“…Although ζ-potential and X-ray measurements corroborate the adsorption of negative amphiphiles to particles of the same charge, the exact mechanism was not discussed . Possibly related to this is the study by Durán-Álvarez . Through streaming potential measurements and molecular dynamics simulations, they found that the adsorption of positively charged dodecyltrimethylammonium bromide (DOTAB) on positively charged calcite depends upon electrostatic screening by counterions and water molecules.…”
Section: In Situ Techniques For Interfacial Particle Assemblya Mater...mentioning
confidence: 99%